The Effect of Leaflet Distribution on Postpartum Mothers' Knowledge of Breast Care at Community Health Centers in the Sulau Community Health Center AreaSouth Bengkulu - Pitri Subani; Yuni Ramadhaniati; Elza Wulandari (Jurnal Kebidanan Manna, 2026)
Background: Breast care during the postpartum period is an essential practice to maintain breast health, prevent breast engorgement, and support the success of exclusive breastfeeding. However, many postpartum mothers still have limited knowledge regarding proper breast care. Educational media, such as leaflets, can be used to improve mothers' knowledge because they are simple, practical, and can be read repeatedly. Objective: This study aimed to analyze the effect of leaflet-based education on postpartum mothers' knowledge of breast care in the working area of Sulau Community Health Center, South Bengkulu Regency. Methods: This study employed a pre-experimental design using a One-Group Pretest–Posttest approach. A total of 27 postpartum mothers were recruited using a total sampling technique. Data were collected using a structured questionnaire administered before and after the leaflet intervention. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test with a significance level of 0.05. Results: Before the intervention, 11 respondents (40.7%) had poor knowledge regarding breast care. Following the leaflet intervention, respondents' knowledge improved, with 17 respondents (63.0%) demonstrating good knowledge and 10 respondents (37.0%) demonstrating moderate knowledge. The results of the Wilcoxon Signed Rank Test indicated a statistically significant effect of leaflet-based education on postpartum mothers' knowledge of breast care (p < 0.05). Conclusion: Leaflet-based education effectively improved postpartum mothers' knowledge of breast care. The use of leaflets as a health education medium can enhance mothers' understanding of proper breast care practices, thereby supporting successful breastfeeding and promoting exclusive breastfeeding.